Eco-Friendly Processing of Momordica Charantia L. Based Chemical Free Functionally Enriched Nectar And Evaluation of Its Nutritional Profile (Bangladesh Journal of Botany, 2022)
The study was conducted to utilize functional attributes of Momordica charantia juice extract by mixing with papaya pulp for imparting yellow-orangecolour of its carotenoids and aonla juice with high Vitamin C to develop Momordica charantia blended functional nectar beverage without any preservative and synthetic food colorant. The ratio of 50 : 25 : 25 of bitter gourd juice extract, aonla juice and papaya pulp with best sensory scores on a nine-point hedonic scale was optimized for the processing of the blended beverage. Functional profile in terms of quality attributes such as reducing sugars (8.39%), DPPH activity (64.20%), total phenolics (41 mg/100 ml), carotenoids (0.58 mg/100 ml), and ascorbic acid (28.8 mg/100 ml) were recorded best in organic honey-based spiced blended nectar. However, charantin content (0.111 mg/100 ml) was found highest in plain bitter gourd beverage. Organoleptic scores and rich functional profile recorded during studies strongly indicated a positive perception of consumers and the need for commercialization.Bangladesh J. Bot. 51(3): 445-453, 2022 (September)